Abangan the best Philippine komiks 2014 - Cham, Rob; David, Adam; Javier, Carljoe; Or, Elbert (Pasay City Visprint, Inc., 2014)
Collection of Philippine graphic novels.
English and Tagalog.
UCWS-3270g donated by Carljoe Javier - May 2014
Keywords: Philippine wit and humor, Pictorial; Comic books, strips, etc. -- Philippines; Philippine fiction